Identifikasi Morfologi dan Molekuler Tanaman Salak di Kecamatan Tanah Grogot Kabupaten Paser Kalimantan Timur - Noor, Sri Maulidah; Effendi, Hamka (Jurnal Pertanian Terpadu, 2022)
Salak is a tropical plant native to Indonesia whose fruit is liked by the public and has good prospects for cultivation. The development of salak in Padang Pangrapat Village, Paser Regency began in 1994, with seeds originating from Central Java so it is better known as "Salak Pondoh Super Paser". This observation aims to determine the identity of salak varieties in Padang Pangrapat Village. Observations were carried out in May – July 2022 by selecting 3 plant samples with 2 comparisons of RIP salak (Pondoh variety and Nglumut variety), the parameters observed were herb, leaf, flower, fruit and production characteristics. The activity was carried out through 2 stages, namely field observations and DNA testing. Based on observations of morphological characterization and DNA testing, the level of similarity between the salak of Padang Pangrapat Village and the Salak of the Nglumut variety was 85.4%.